Orientacja procesowa w zarządzaniu a narzędzia integracji systemów - Polak, Przemysław (A process orientation in management and systems integration tools, 2006)
Contemporary process modeling tools and integrated information systems provide comprehensive support for modeling, designing and managing organizational business processes. However, they do not provide such direct support of interorganizational processes. An approach to processes implemented in such solutions like MS BizTalk or ebXML do not reflect requirements of modern management concepts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 133-141